Applying Biometric Technology in School Attendance and Security Management - Mufron, Ali; Wei, Zhang (Al-Hijr: Journal of Adulearn World, 2024)
In today's digital era, security and efficiency in attendance management in the school environment are very important. Biometric technology has become a new trend in improving security and optimizing the attendance recording process, replacing manual systems prone to errors and fraud. This research aims to analyze the effectiveness of applying biometric technology in school attendance and security management. Specifically, this research focuses on evaluating how this technology can reduce cheating, increase the accuracy of attendance data, and strengthen school security systems. This research uses quantitative methods with a case study approach at five schools implementing a biometric system. Data was collected through surveys of school administrators and direct observation of the registration and identity verification processes at these schools. Data analysis was carried out using descriptive and inferential statistics. This research shows that using biometric technology significantly increases the efficiency and accuracy of the attendance recording system. Student attendance is recorded quickly and accurately, with virtually no cheating. This technology also strengthens the security system by ensuring that only verified individuals can access school facilities. This research concludes that applying biometric technology in school attendance and security management has proven very effective. This technology optimizes attendance and improves security, providing a safe environment for students and staff. The research recommends wider adoption of biometric technology in other schools to improve security and operational efficiency.